Animal Magnetism, Psychiatry and Subjective Experience in Nineteenth-Century Germany: Friedrich Krauß and his Nothschrei. Issue 1 (10th December 2015) - Brückner, Burkhart
Abstract : Friedrich Krauß (1791–1868) is the author of Nothschrei eines Magnetisch-Vergifteten [Cry of Distress by a Victim of Magnetic Poisoning] (1852), which has been considered one of the most comprehensive self-narratives of madness published in the German language. In this 1018-page work Krauß documents his acute fears of 'mesmerist' influence and persecution, his detainment in an Antwerp asylum and his encounter with various illustrious physicians across Europe. Though in many ways comparable to other prominent nineteenth-century first-person accounts (eg. John Thomas Perceval's 1838 Narrative of the Treatment Experienced by a Gentleman or Daniel Paul Schreber's 1903 Memoirs of my Nervous Illness ), Krauß's story has received comparatively little scholarly attention. This is especially the case in the English-speaking world. In this article I reconstruct Krauß's biography by emphasising his relationship with physicians and his under-explored stay at the asylum. I then investigate the ways in which Krauß appropriated nascent theories about 'animal magnetism' to cope with his disturbing experiences. Finally, I address Krauß's recently discovered calligraphic oeuvre, which bears traces of his typical fears all the while showcasing his artistic skills. By moving away from the predominantly clinical perspective that has characterised earlier studies, this article reveals how Friedrich Krauß sought to make sense of his experience by selectively appropriating both orthodox and non-orthodox forms of medical knowledge. In so doing, it highlights the mutual interaction of discourses 'from above' and 'from below' as well as the influence of broader cultural forces on conceptions of self and illness during that seminal period.